EVALUATION OF EXPRESSION OF 4 MIRNAS IN CYTOLOGICAL SAMPLES AS AN ADDITIONAL METHOD OF CERVICAL CANCER DIAGNOSIS - P. A. Arkhangelskaya; R. B. Samsonov; T. A. Shtam; M. S. Knyazeva; M. K. Ivanov; S. E. Titov; N. N. Kolesnikov; E. V. Bakhidze; I. V. Berlev; A. А. Mikhetko; S. L. Vorobyev; A. V. Malek (Опухоли женской репродуктивной системы, 2017)
Introduction. Cervical cancer is the 4th most common cancer among women. The main screening method for cervical cancer is cytological examination of the cervical epithelium. This method allows to evaluate the level of cervical dysplasia (malignant potential) but it has several limitations and flaws. Development and implementation of new methods of molecular and genetic analysis in clinical practice can increase informational value of the traditional cytological examination and therefore objectivity in choosing treatment options.Objective is to develop and verify a new method of differential diagnosis of severe intraepithelial dysplasia and invasive cervical cancer.Materials and methods. The method is based on analysis of small non-coding RNA molecules (miRNAs) extracted from the material of traditional Pap smears. Based on literature search, 18 “marker” microRNA molecules were chosen and their expression levels were estimated in 166 samples of Pap smears from cervical canals with different cytological diagnoses. The analysis was performed using reverse transcription polymerase chain reaction.Results. Estimation of ratios between expression levels of miRNA pairs: 126/375; 20а/375; 126/145 allows to differentiate with high confidence borderline states of severe intraepithelial dysplasia and invasive cervical carcinoma (coefficients of quantitative interpretation of the error curve were 0.8, 0.75, 0.72, respectively).Conclusions. Analysis of miRNAs in Pap smear samples is a promising additional method of cervical cancer diagnosis. The method is objective and can be proposed as a supporting technique in cases when cytological examination doesn’t allow to differentiate between borderline pathological states of the cervical epithelium. Implementation of the method in clinical practice requires methodological optimization and additional validation using more clinical material.